Collaborative Governance Dalam Optimalisasi Pelaksanaan Kebijakan Pembelajaran Daring Di Masa Pandemi Covid - Astuti, Retno Sunu; Taufik, (Asketik: Jurnal Agama dan Perubahan Sosial, 2021)
The Covid-19 pandemic has changed the world's learning system, from face-to-face to online (online). The transition of this system is a challenge that must be faced by education providers. This study aims to map the challenges faced in online learning, and analyze the use of a collaborative approach to deal with them. This research uses a qualitative descriptive approach, by utilizing literature and articles that are traced through literature studies. The results of the study found three challenges faced in online learning, namely: technology, socio-economics, and digital competence. There are five stakeholders in online learning collaboration during the COVID-19 pandemic, namely the government, the private sector, NGOs, universities, and the mass media. These stakeholders have their respective roles according to their capacities. Collaboration can work well by directly involving stakeholders in decision making, built through intensive communication between stakeholders in delivering creative and innovative ideas to solve online learning problems.